2010
DOI: 10.1111/j.1365-2702.2009.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a guideline for pressure ulcer prevention in home care: pretest–post‐test study

Abstract: Aims and objectivesTo investigate the effect of the implementation of a patient and family education programme for pressure ulcer prevention in an organisation for home care nursing on guideline adherence and on prevalence and severity of pressure ulcers and to examine the determining factors for the application of measures for pressure ulcer prevention.Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
7
0
8
Order By: Relevance
“…Studies analyzing the ADL and PU are scarce, and the data of this study are consistent with the trend in the literature that investigated the issue (22)(23) . A study with institutionalized elderly found that for each increase of one point on the scale of ADL, the risk of PU increases 1.38 times (14) .…”
Section: Characterization Of People With Cancer In Home Palliative Caresupporting
confidence: 77%
“…Studies analyzing the ADL and PU are scarce, and the data of this study are consistent with the trend in the literature that investigated the issue (22)(23) . A study with institutionalized elderly found that for each increase of one point on the scale of ADL, the risk of PU increases 1.38 times (14) .…”
Section: Characterization Of People With Cancer In Home Palliative Caresupporting
confidence: 77%
“…It may be attributed to the effect of program and practices that lead to an increase in the knowledge of the practitioners during the program period since the professionals take many sessions that contribute for practicing experience. It agrees with paquay et al (2010) (37) who found that nurse`s adherence to PU guidelines was significantly improved after implementing of an educational program. This is also supported by the work of Smith & Waugh et al (2009) (38) , who used descriptive study among 435 registered nurses.…”
Section: A Study In Turkey By Tweed and Tweed (2008)supporting
confidence: 81%
“…This is noteworthy because while clinical judgement is recognised as an important component of risk assessment, research has shown that clinical judgement in isolation is not an adequate or reliable predictor of pressure injury risk [50,51]. Judgement of a patient’s risk status is an important basis for deciding to implement preventive measures [37]. Reasons for this favourable change occurring, might be because risk assessment documentation is included within a patient’s medical notes.…”
Section: Discussionmentioning
confidence: 99%
“…Prentice and Stacey [25] found that introduction of pressure injury clinical practice guidelines combined with a comprehensive, multifaceted education pressure injury program, for junior medical and nursing staff that included peri-operative nurses, significantly reduced pressure injury prevalence. Other combinations of multi-faceted strategies have similarly reported improvements in knowledge and practice [31,37]. Some studies have reported mixed results of strategies targeting nurses’ knowledge and documentation that included an educational component, with improvements on some domains such as documentation practices [38] or on reported use of risk assessment and prevention strategies [39] or no statistically significant improvements at all [21].…”
Section: Introductionmentioning
confidence: 99%